Budget Impact Analysis of Fecal Microbiota Spores, Live-brpk (Formerly SER-109) for Recurrent Clostridioides difficile Infection in the United States - Michele Wilson; Yoav Golan; Dianne Nguyen; Morteza Yazdani; Alpesh N. Amin (Infectious Diseases and Therapy)
Abstract Introduction Fecal microbiota spores, live-brpk (hereafter VOS) is a microbiota-based orally administered therapeutic approved by the United States Food and Drug Administration for prevention of recurrent Clostridioides difficile infection (rCDI) following standard-of-care (SoC) antibiotics for the treatment of rCDI in patients aged ≥ 18 years. The study objective was to estimate the budget impact of introducing VOS within a hypothetical United States (US) health plan. Methods A model was developed estimating the health plan budget impact of adding VOS to SoC compared with SoC alone for rCDI. Input data were from the published literature. Uptake of VOS was assumed at 10%, 20%, 30%, and 40% for recurrences 1 through 4, respectively. Annual and per-member per-month (PMPM) costs (2023 US dollars) were estimated from a health plan perspective. Scenario analyses considered different VOS uptake rates and use of fecal microbiota, live-jslm (hereafter RBL). Results Including VOS on a formulary for rCDI was found to reduce overall annual costs in a 1-million-member commercial plan by US$42,328. VOS increased pharmacy costs (US$0.0820 PMPM), and these pharmacy costs were offset by other medical cost savings (−US$0.0856 PMPM) such that including VOS on a formulary was cost-saving at US$0.0035 PMPM. With these cost savings, introducing VOS prevented an estimated 27 recurrences among 225 individuals with rCDI. Scenario analyses indicated greater and/or earlier VOS uptake generates more cost savings owing to recurrence prevention, and that VOS was more cost-saving than RBL. Conclusions Treatment with VOS is anticipated to reduce recurrences and health plan costs for those with rCDI. Using VOS earlier is expected to increase cost savings. Graphical abstract available for this article. Graphical Abstract